2020
DOI: 10.1101/2020.10.27.356873
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of fasting blood glucose, serum electrolyte, albumin, creatinine, urea and lipid profile among hypertensive patients and non-hypertensive participants at wolaita sodo university teaching and referral hospital, SNNPR, Ethiopia

Abstract: Background: Hypertension is a silent killer that requires long term management to avoid complications.  It is one of major public health problem in developing counties like Ethiopia. Hypertension increases the risk of morbidity and mortality and has negative consequences on the cognitive and physical fitness of productivity in adults. Objective: To assess fasting blood glucose, serum electrolyte, albumin, creatinine, urea, and lipid profile among hypertensive patients and non-hypertensive participants at wol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…All blood samples were collected after having an 8–12 h fasting state at the Nutrition and Genomics Laboratory of TUMS. Moreover, fasting blood sugar (FBS), TG, total cholesterol level, low-density lipoprotein (LDL), and HDL were measured according to standard protocols [ 17 ]. All of which were measured at the Bionanotechnology laboratory, Tehran University of Medical Science.…”
Section: Main Textmentioning
confidence: 99%
“…All blood samples were collected after having an 8–12 h fasting state at the Nutrition and Genomics Laboratory of TUMS. Moreover, fasting blood sugar (FBS), TG, total cholesterol level, low-density lipoprotein (LDL), and HDL were measured according to standard protocols [ 17 ]. All of which were measured at the Bionanotechnology laboratory, Tehran University of Medical Science.…”
Section: Main Textmentioning
confidence: 99%
“…In addition, hypertension may induce microvascular dysfunction through an increase in the production of superoxide anions and hydrogen peroxide (levels of reactive oxygen species) and a decrease in nitric oxide synthesis [ 42 , 43 ] which may result in insulin resistance and hyperglycemia. Previous studies also documented that biomarkers of endothelial dysfunction were found to be independent predictors of hyperglycemia [ 38 ]. This implies hypertension would contribute to the pathophysiology of type II diabetes development.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, higher blood pressure among hypertensive cases would result in increased renal tubular reabsorption and increased arterial pressure. This would also lead to higher values of glomerular capillary wall stress, activation of neuro-humoral systems, and increased serum lipid level among cases [ 38 ]. This implies that high TG, high LDL-c, and low HDL-c levels are associated with increased blood pressure and atherosclerosis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A validated 147-items semi-quantitative food frequency questionnaire (FFQ) with high validity and reliability was used (32) by an expert to evaluate the dietary intake of the participants. Aimed at the calculation of macro-and micronutrient content, grams of foods were entered into NUTRITIONIST IV software (version 7.0; N-Squared Computing, Salem, OR) (33).…”
Section: Dietary Assessmentsmentioning
confidence: 99%
“…Blood samples were prepared after 10-12 hours night fasting at the nutrition and Biochemistry laboratory of the school of nutritional Sciences and Dietetics, TUMS. Additionally, fasting blood sugar (FBS), liver enzymes (alanine aminotransferase (ALT) and aspartate aminotransferase (AST)), Highsensitivity C-reactive protein (hs-CRP), Monocyte chemoattractant protein-1 (MCP-1), interleukin 1 beta (IL-1β) and transforming growth factor beta1(TGF-β1), serum lipids and lipoproteins ,triglycerides (TG), total cholesterol level, low-density lipoprotein (LDL), and high-density lipoprotein (HDL) were measured according to standard protocols (32) Genotyping DNA was extracted for genotyping the Cav-1 polymorphisms from total blood via a Mini Columns kit (Type G; Genall; Ex gene). The polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique was hired to investigate Cav-1 polymorphisms (rs3807992) in gene fragments (major allele G and minor allele A).…”
Section: Biochemical Measurementsmentioning
confidence: 99%